Comparison of the effects of coblation and curettage adenoidectomy on adenoid regrowth - Gul, Fatih; Kayabasi, Serkan (Annals of Medical Research, 2021)
Aim: To investigate whether there is a relationship between coblation and curettage adenoidectomy techniques in adenoid recurrence. Material and Methods: An electronic medical database was used to identify the records of 84 children who were performed adenoidectomy without tonsillectomy between January 2016 and January 2019. Patients who had adenoid hypertrophy without a history of revision surgery and underwent coblation or curettage adenoidectomy without tonsillectomy were included in the study. Operation notes were recorded. Adenoid regrowth was evaluated by flexible nasal endoscopy in patients who completed at least a 1-year follow-up period. Results: 51 and 33 patients met the inclusion and were comprised of coblation and curettage groups, respectively. The mean operative time was 14.5±5.1 min in the curettage group and 23.3±11.4 min in the coblation group (p=0.001). The mean intraoperative blood loss was 5.75±3.6 ml in the coblation group, and 11.58±7.2 ml in the curettage group (p=0.007). At the end of a 1-year follow-up period, adenoid regrowth rate was observed in 5.66% in the curettage group and 2% in the coblation group and this difference was statistically significant (p=0.027). Conclusion: Coblation adenoidectomy represents a reliable and highly effective method that has a low incidence of regrowth and less intra-operative bleeding but has a longer operation time in comparison with conventional cold curettage adenoidectomy.Keywords: Curettage adenoidectomy; coblation adenoidectomy; adenoidal regrowth.
Keywords: Curettage adenoidectomy; coblation adenoidectomy; adenoidal regrowth.